2021
DOI: 10.3390/ijms222111809
|View full text |Cite
|
Sign up to set email alerts
|

Role of Integrins in Sperm Activation and Fertilization

Abstract: In mammals, integrins are heterodimeric transmembrane glycoproteins that represent a large group of cell adhesion receptors involved in cell–cell, cell–extracellular matrix, and cell–pathogen interactions. Integrin receptors are an important part of signalization pathways and have an ability to transmit signals into and out of cells and participate in cell activation. In addition to somatic cells, integrins have also been detected on germ cells and are known to play a crucial role in complex gamete-specific ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 129 publications
(200 reference statements)
0
11
0
Order By: Relevance
“…25 Integrin α6/β1 is a determinant of sperm function. 26 In the present study, Shengjing recipe increased the levels of FSH and T, but the exact clinical significance of these changes is unknown since the values were within the normal values at baseline and after treatment. Still, these changes were also observed in previous studies.…”
mentioning
confidence: 56%
“…25 Integrin α6/β1 is a determinant of sperm function. 26 In the present study, Shengjing recipe increased the levels of FSH and T, but the exact clinical significance of these changes is unknown since the values were within the normal values at baseline and after treatment. Still, these changes were also observed in previous studies.…”
mentioning
confidence: 56%
“…Tetraspanins generally act within the tetraspanin web, a functional multi-molecular complex composed of different tetraspanins and their interacting partner molecules (Zuidscherwoude et al 2015 ). In cell membranes, including those of gametes, tetraspanins usually form complexes with integrins (Maecker et al 1997 ; Berditchevski and Odintsova 1999 ; Stipp 2010 ; Merc et al 2021 ), whose functions also regulate (Hemler 2005 ). Integrins are the adhesion receptors that act as transmembrane linkers between the extracellular matrix and the actin cytoskeleton, with the ability to transmit outside-in and vice versa signaling (Longhurst and Jennings 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Acropora , its involvement in sperm and egg interactions ( Iguchi et al, 2007 ) and its divergence in terms of sequences and expression ( Knack et al, 2008 ) have been reported. The ADAM family of disintegrins and metalloproteases includes ADAM2 (a “fertilin”), which is implicated in sperm–egg binding via integrin—ADAM binding ( Evans, 2001 ; Merc et al, 2021 ). However, the function of integrins and ADAM in the fertilization of coral have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%